Analysis of The Efficiency of Fiscal Policy on Economic Growth in 4 Asean Countries: Data Envelopment Analysis (DEA) Approach - Aisyah Farah Amalia; Aprilia Dita Cahyani; Oky Tri Wahyu; Mardina Oktavia Wulandari; Ainul Yakin; Dimas Andika Jaya; Rendy Arifaqih (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
The purpose of this study is to investigate the effectiveness of fiscal policy on economic growth in four ASEAN countries, namely: Indonesia, Malaysia, the Philippines and Vietnam during 2014–2024. This study is inspired by the discrepancy of fiscal capacity and economic growth between its members within ASEAN, hence it is important to know more specifically how effective tax revenue in creating economic growth. The original contribution of this research is the use of DEA to measure the efficiency of fiscal policy for generating state revenue among ASEAN countries. It has not been researched well as a field. The primary contribution of this paper is to contribute to the empirics of efficiency performance in a quantitative manner as scale and technical efficiency comparisons between economies in ASEAN region. The research approach follows a descriptive quantitative dogma and relies on secondary data obtained from the World Bank and IMF. The input variables are tax revenue, tax ratio and VAT, the output is economic growth (GDP growth). The findings indicate that technical fiscal efficiencies in most of ASEAN countries are somewhat successful. Nevertheless, scale efficiency is still quite low, indicating the current fiscal policy is not yet optimal for economic growth. Finally, the result implies that public resource management should be emphasizing more on institutional capacity and the relevance of fiscal operations in designing budgetary policy as a means of ensuring sustainable economic growth. Keywords: fiscal efficiency, economic growth, ASEAN, taxes, DEA